The phonology of voicing and aspiration in Amdo Tibetan - Green, R. Jeffrey (2024)
Rebgong Amdo Tibetan is that variety of Amdo Tibetan (ISO 639-3 code adx) spoken in Tongren County, Huangnan Tibetan Autonomous Prefecture, Qinghai Province, in north-west China. Most analyses of Amdo Tibetan dialects report a marginal three-way contrast between voiced, voiceless unaspirated, and voiceless aspirated stops and affricates at each place of articulation. The present analysis posits only two contrastive series for Rebgong Amdo Tibetan, in agreement with Janhunen & Kalsang Norbu’s (1999) analysis of rDo-sbis Amdo Tibetan. Reports that many other Amdo dialects show the same restrictions on the distribution of these sounds suggest that this analysis might likewise apply to other varieties of Amdo Tibetan. Comparison with discussions of Classical Tibetan and Proto-Tibeto-Burman further suggest that Amdo Tibetan may have always only had this two-way contrast.